Lifting regimes of thermal plumes in vertical layer - Gavrilov, Konstantin Alekseevich; Demin, Vitaliy Anatolievich; Popov, Evgeniy Andreevich (Computational Continuum Mechanics, 2013)
Theoretical investigation of the dynamics of free thermal plumes in a thin vertical layer has been performed for the case of a cavity heated from below by means of a dotted thermoelement. Three-dimensional numerical modeling has been carried out with the help of package OpenFOAM. This integrable platform is meant for calculations in the area of continuous media mechanics. Four basic plume growth types (viscous-diffusive, inviscid-diffusive, viscous-nondiffusive and inviscid-nondiffusive regimes) are found. Animated images for various lifting regimes are obtained to observe the time-dependent behavior of thermal plumes. The stages of plume formation in a relatively thin layer, its steady lifting and deceleration by the top boundary have been analyzed for different profiles of the plume front. The interaction of two synchronous plumes is studied numerically, and the formation of a common thermal front is demonstrated.
Keywords: convective jet in the early stage (thermal plume); thin vertical layer; numerical modeling; 3D-calculations; package OpenFOAM; interaction of plumes